2004
DOI: 10.2307/3583186
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Being Served Least by Family Planning Providers? A Study of Modern Contraceptive Use in Ghana, Tanzania and Zimbabwe

Abstract: This study was conducted to identify the poorest and other vulnerable sub-groups being served least by family planning providers. The study was set in three countries in sub-Saharan Africa, namely, Ghana, Tanzania and Zimbabwe. This region generally has a low but increasing uptake of modern contraceptive methods. As the use of family planning providers increases, there is a need to understand who is not being served and why. Logistic regression analyses of demographic and health survey data were conducted to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 12 publications
6
20
4
Order By: Relevance
“…Consistent with expected relationships for demand and access, the few studies undertaken to date with a focus on socioeconomic issues indicate that contraception rates are lower in poor countries and, within the limited set of countries analyzed, lower in poor women [21–25]. This study demonstrates that despite increases in national averages over time, the use of modern contraception by the absolute poor remains low, and the gaps in use across wealth quintiles persist and are increasing.…”
Section: Discussionsupporting
confidence: 64%
“…Consistent with expected relationships for demand and access, the few studies undertaken to date with a focus on socioeconomic issues indicate that contraception rates are lower in poor countries and, within the limited set of countries analyzed, lower in poor women [21–25]. This study demonstrates that despite increases in national averages over time, the use of modern contraception by the absolute poor remains low, and the gaps in use across wealth quintiles persist and are increasing.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, among those married or living together at the time of the surveys and who were current users of FP methods, more than 82% of adolescents and 71% of young women took their decision about FP (18). Contrary to our nding, other studies found that married women had a signi cant relationship with the use of modern FP method and that adolescents and young women who were married or living together with a partner were more likely to use modern FP methods than those who were not married (or did not have a partner) (32,42).…”
Section: Factors Associated With the Use Of Modern Fp Methodscontrasting
confidence: 99%
“…However, in this study, married adolescents and young women were less likely to use modern FP methods than unmarried participants. Others studies conducted in Ghana, Ghana, Tanzania and Zimbabwe found also the signi cant relationship between modern FP methods use adolescent marriatal status (32,42). Moreover, among those married or living together at the time of the surveys and who were current users of FP methods, more than 82% of adolescents and 71% of young women took their decision about FP (18).…”
Section: Factors Associated With the Use Of Modern Fp Methodsmentioning
confidence: 95%
“…For instance, wealthier and educated women are expected to be more conscious about their health and that of their families hence more likely to use family planning methods. Some previous studies have also established significant positive relationship between socioeconomic status and contraceptive use among women (Tuoane et al, 2003, Curtis and Neitzel, 1996, Clement and Madise, 2004 Asiimwe et al (2013).…”
Section: Discussionmentioning
confidence: 98%